Geology and geochemistry of ultramafic rocks in the Lake of the Woods Greenstone Belt - Boucher, Chanelle (My University, 2019)
The Archean komatiites of the Lake of the Woods greenstone belt, Kenora, Ontario formed on the western extension of the Superior Province southern margin and have not been studied using modern analytical methods. Although Archean plate tectonic processes have been the subject of decades of research, the nature of these processes remains the subject of considerable debate. Recent work has investigated the link between komatiites and Archean subduction zones. Komatiites are widespread in Archean terranes and together with spatially associated tholeiitic basalts form an important part of many Late Archean greenstone belts, therefore a better understanding of Archean geodynamic processes and comparison to modern day processes is required. Detailed mapping in the Upper Keewatin Assemblage identified komatiites on the southern margin of the Long Bay Group. The komatiites are typically metamorphosed to upper greenschist facies and include a variety of schists that do not show any preserved primary textures or mineralogy. Polyhedrally jointed flow tops were observed in rare locations. Mineral assemblages include dominantly anthophyllite-tremolite-chlorite and serpentine-tremolite-chlorite schists, as well as lesser talc-tremolite-chlorite schists. These units are moderately to intensely foliated with chlorite and lesser amphibole defining the foliation and also include randomly oriented bladed amphibole grains that typically have tremolite cores and anthophyllite rims. The amphiboles show a chemical transition from core to rim with a loss in Ca as anthophyllite appears. Accessory phases include chromite, magnetite, ilmenite and apatite. Ultramafic rocks are very fine-grained and mineralogy has been described using a compilation of petrography, x-ray diffraction and scanning electron microscope analysis. [...]
Keywords: Komatiites; Whole rock geochemistry; Ultramafic rocks